RELASIONALITAS ANAK RONA-ANAK WINA DALAM UNGKAPAN TOE SALANG TUAK-WAE TEKU TEDENG: TINJAUAN FILSAFAT ARMADA RIYANTO - Hamat, Yulianus Evantus; Riyanto, F. X. Armada (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The main focus of this writing is to explore the wealth of local wisdom in Manggarai, namely the philosophical meaning behind Go’et Toe salang tuak-wae teku tedengin the relationship between Anak Rona and Anak Wina. The process of exploration and deepening is carried out in the light of Armada Riyanto's Philosophy of Relationality. In this context, the philosophical concept of Armada Riyanto serves as a dissecting tool that aids the author in understanding the go’et Toe salang tuak-wae teku tedengwithin the framework of relationality. This deepening effort is based on the phenomenon of a shift in the meaning of belis that has an impact on the fracture of their relationship. In response to this phenomenon, the author introduces the philosophical concept of go’et Toe salang tuak-wae teku tedengas an effort to clarify the perspective on the meaning of belis among the Manggarai people. The method used is a qualitative approach, namely literature review. This writing finds that the relationship between Anak Rona and Anak Wina will be harmonious when the understanding of belis is not reduced to an attempt to impoverish one party but rather to the respect for the mother's womb that has given birth to life in this world.